Assessment of the Impact of Overeating on Obesity Central Health Perspective: A Study of Takhrij Hadith - Najmi, Muhammad Nur; Aliansyah, Muhammad (Journal of Takhrij Al-Hadith, 2024)
The purpose of this study was to discuss the impact of overeating on obesity from a central health perspective. This research uses a qualitative approach by applying descriptive-analytical methods. The formal object of this research is the science of hadith, while the material object is the narrated hadith of Ibn Majah No. 3340. The results and discussion of this research show that the status of hadith quality hasan li ghairihi who meets the qualifications in the practice of a hadith. This study concluded that the hadith narrated by Ibn Majah No. 3340 is relevant to be used as a reference in maintaining the body to be healthier.